Comparative analysis of key aroma compounds in air-frying roasted pork from five species - Lin Li; Pingping Huang; Rujie Yang; Jingyu Li; Yuping Zhang; Junke Li; Jianjun Li; Jianmei Zhang; Nigel P. Brunton; Huan Liu; Xiangru Wei (Food Chemistry: X)
The popularity of roasted pork among Chinese consumers is largely attributed to its rich aroma profile. However, the suitability of different pork species for roasting remains uncertain. In this study, the effect of various pork species on the aroma profiles of roasted pork was systematically investigated using gas chromatography-olfactometry-mass spectrometry (GC-O-MS). The results indicated that the roasted pork from five different species exhibited rich roasty, meaty, and fatty notes. Fifty-two aroma compounds were identified, with seven key odorants, including pyrazines and aldehydes, being recognized as primary contributors to the aroma. The orthogonal partial least squares discriminant analysis (OPLS-DA) effectively distinguished the aroma profiles of the five pork species. Twelve aroma compounds displayed variable importance in projection (VIP) scores exceeding 1, with butyrolactone being identified as a potential biomarker. Among the species, Tibetan and Min pigs were found to be the most suitable for roasting, with Min pigs showing particular promise.